Pertumbuhan Penduduk Perkotaan dan Perkembangan Pola Distribusinya pada Kawasan Metropolitan Surakarta - Fadjar Hari Mardiansjah; Wiwandari Handayani; Jawoto Sih Setyono (Department of Urban and Regional Planning, Diponegoro University, 2018)
Urbanization has brought rapid changes and transformations in many aspects of urban processes of many developing countries, including in spatial aspect, in the form of extended spatial formation of the cities into the surroundings, in order to meet the needs of economic and productive processes as well as those of social and consumption processes. Using the case of the growth of Surakarta Metropolitan, this paper aims to deepen understanding on the spatial process of urban population growth in the peripheries of secondary metropolitan that based on medium city size in Java, which is considered as one of the most densest populated in the world. The article will show the process of metropolitanization in Surakarta Metropolitan, in which influenced of its limitness of the administrative jurisdiction of the core area, the the growth extends into the surrounding areas. The analysis employs a time serial analysis by utilizing the national censuses population data from 1990 to 2010, The result shows that the urbanization process in Surakarta leads into a extended spatial form which also characterized by a fragmented phenomena. The spatial urban formation formed by such a process consist of a combination of some extensions of the previous urban areas and the formation of new urban centers that approached and merged one to each other in the long run. This process need to be understood as urbanization process is also a major contributors that shape the resource allocation and consumption of resources in the metropolitan and the surrounding areas. For Indonesia, the understanding of these processes will be very beneficial for the formulation of regional collaboration strategies in developing sustainable urbanization in the future.